Manjapuik Barokah Ramadhan: Enhancing Qur'anic Literacy And Ibadah Practices In Sago Salido Village Through Service Learning - Tumanggor, Ilham; Hasibuan, Muhammad Syarif Muda; Muhartrisia, Yurahmi; Dongoran, Irham (ASSUNNAH PRESS, 2025)
This community service program was implemented to enhance Qur'anic literacy and strengthen ibadah practices among the community around Jabal Rahmah Mosque and Rumah Tahfiz Qur'an (RTQ) Ibnu Mas'ud, Nagari Sago Salido, Pesisir Selatan Regency, West Sumatra, through a Service Learning approach. The